316 Mobile Phone Cultures of Healthcare Workers: A Possible Source for Nosocomial Infections. (11th January 2018) - Naveed, Muhammad
Abstract: Materials and Method: This cross-sectional study was conducted at the pathology department of Allama Iqbal Medical College, Lahore, Pakistan, from July 2016 to January 2017. Using sterile cotton swabs, we took 209 samples from healthcare workers (HCWs) at Jinnah Hospital, Lahore, Pakistan. Each swab was first moistened with normal saline, then rotated over the surface of both sides and the keypad of the subject's mobile phone. All swabs were cultured on blood agar, MacConkey agar, and chocolate agar using standard microbiological techniques. Organisms were identified by colonial morphology, Gram staining, catalase test, oxidase test, and complete biochemical profile. Results: Out of 257 mobile phones, 169 (65.76 %) were colonized with bacterial isolates. Staphylococcus epidermidis followed by Staphylococcus aureus were predominantly isolated from 36.09% and 23.07% of all mobile phones, respectively. Methicillin-resistant Staphylococcus aureus and methicillin-resistant Staphylococcus epidermidis were identified in 8.74% and 3.9 % of the mobile phones, respectively. Other microbes identified were 22 Acinetobacter species (13.01%), 15 Bacillus species (8.87%), 11 Enterococcus species (6.5%), six Micrococcus species (3.5%), five Escherichia coli (2.95%), three Pseudomonas aeruginosa (1.77%), three Aspergillus species (1.77%), two Klebsiella species (1.18%), one Diphtheroids species (0.59%), and one Enterobacter aerogenes (0.59%). Conclusion: Mobile phones usage in the hospital setting poses a risk of transmission of a variety of bacterial agents including such multidrug-resistant pathogens as methicillin-resistant S aureus . These results showed that 82.04 % of HCWs' mobile phones were contaminated with various types of bacterial isolates. Mobile phones used by HCWs in daily practice may be a source of nosocomial infections in hospitals.